Evolution of viral RNA in a Chinese patient to interferon/ribavirin therapy for hepatitis C - Wen, Xian-Zi; Chen, Zhi-Hai; Wei, Ya-Zhi; Ji, Jia-Fu (Chinese Journal of Cancer Research; Vol 24, No 4 (December 07, 2012): Chinese Journal of Cancer Research, 2012)
Objective: The combination of interferon (IFN) and ribavirin (RBV) is the standard therapy for hepatitis C virus (HCV) infection. HCV genotype 2a has proved more amenable to the therapy, but its efficacy is yet limited. This study aimed to investigate the mechanism of the poor response in a case of HCV genotype 2a infection. Methods: We analyzed dynamic change of HCV RNA from a patient, infected with HCV genotype 2a, showing a poor virological response to IFN/RBV as judged 12 weeks after initiation of the therapy by HCV clone sequencing. Then we constructed subgenomic Japanese fulminant hepatitis-1 (JFH1) replicon and different chimeric replicons with humanized Gaussia luciferase gene. The chimeric replicons were derived from subgenomic JFH1 replicon, in which the NS5A region was replaced by the patient’s sequence from the pre/posttreatment, and the chimeric replicons’ susceptibility to IFN were evaluated by relative Gausia Luciferase activity. Results: The pretreatment HCV sequences appeared almost uniform, and the quasispecies variation was further more simplified after 12 weeks of therapy. Besides, the quasispecies variation seemed to be more diversified in the NS5A, relatively, a region crucial for IFN response, and each of chimeric replicons exhibited distinct response to IFN. Conclusions: During the course of the chronic infection, HCV population seems to be adapted to the patient’s immunological system, and further to be selected by combination of IFN/RBV therapy, indicating quasispecies may completely eliminated by addition of other drugs with targets different from those of IFN. In addition, each different response of chimeric replicon to IFN is most likely related to amino acid changes in or near the IFN-sensitivity determining region (ISDR) of NS5A during chronic infection and IFN/RBV therapy.